Priority areas for conservation alone are not a good proxy for predicting the impact of renewable energy expansion - Pérez García, Juan M. (2022)
There is broad consensus that increasing the use of renewable energies is effective to mitigate the global climate crisis. However, the development of renewables may carry environmental impacts, and their expansion could accelerate biodiversity loss (1). However, Dunnett et al. (2) haverecently estimated a minimal overlap between renewable energy expansion and important conservation areas (ICAs; i.e., protected areas, key biodiversity areas, wildernessareas) (sensu ref. 2), suggesting that these infrastructures would not significantly affect biodiversity conservation if properly planned and regulated. Assessing the impacts of renewables on biodiversity only in terms of their spatial overlap with ICAs ignores that these impacts on species and functional groups are asymmetric. Long-lived species are highly vulnerable to the loss of specific habitats or to nonnatural mortality, and these factors should be considered when studying conflicts between renewables and biodiversity (3). For instance, one of the most concerning impacts of wind farms, which have dramatically multiplied worldwide in recent years (Fig. 1 A and B), is the nonnatural mortality of highly mobile flying species, such as birds (4) and bats (5), due to collisions with turbines (Fig. 1 C and D). Many of these species spend a large part of their life cycle outside ICAs (6, 7), where mortality caused by infrastructures can extirpate populations at regional scales and even within ICAs (8). Consequently, thinking that we canrely only on ICAs for the protection of these species is very risky and may obscure the real magnitude of the threat posed by renewable energy development.